2016
DOI: 10.1158/1055-9965.epi-15-1088
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Progressively Reduced Nicotine Content Cigarettes on Smoking Behaviors, Biomarkers of Exposure, and Subjective Ratings

Abstract: Background The U.S. FDA has the authority to reduce cigarette nicotine content if found to benefit public health. Reduced nicotine content (RNC) cigarette use does not appear to increase harm exposure, but studies have not rigorously assessed smoking behavior or utilized a comprehensive panel of biomarkers. This study examined the effects of progressively decreasing RNC cigarettes on smoking behaviors, biomarkers of exposure, and subjective ratings. Methods 158 daily, non-treatment-seeking smokers participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 29 publications
3
68
0
Order By: Relevance
“…The study used a similar study design as used by Eissenberg et al 15 for assessing e-cigarettes, and by Goniewicz et al 21 and others to examine smoking behavior differences across tobacco products. 22,23 The study was conducted in 3 sessions: Day 1 (usual brand cigarette smoking) and Days 5 and 10 (single brand of e-cigarette use). Following Day 1, participants were required to refrain from using regular cigarettes and were asked to use the provided brand of e-cigarette; an assessment of breath carbon monoxide (CO) was conducted to verify refraining from cigarette use (≤10 ppm on Day 5 and Day 10), using a cut-off for cigarette smoking abstinence often used in clinical trials.…”
Section: Methodsmentioning
confidence: 99%
“…The study used a similar study design as used by Eissenberg et al 15 for assessing e-cigarettes, and by Goniewicz et al 21 and others to examine smoking behavior differences across tobacco products. 22,23 The study was conducted in 3 sessions: Day 1 (usual brand cigarette smoking) and Days 5 and 10 (single brand of e-cigarette use). Following Day 1, participants were required to refrain from using regular cigarettes and were asked to use the provided brand of e-cigarette; an assessment of breath carbon monoxide (CO) was conducted to verify refraining from cigarette use (≤10 ppm on Day 5 and Day 10), using a cut-off for cigarette smoking abstinence often used in clinical trials.…”
Section: Methodsmentioning
confidence: 99%
“…Although smokers may attempt to compensate when they first try VLNC cigarettes, numerous studies have shown that most smokers do not compensate after the first few cigarettes5 34 35 and that biomarkers of smoke exposure do not increase when participants are switched to VLNC cigarettes 4 5 8 9 16 17. One limitation of clinical trials suggesting little or no compensation is that smokers could easily purchase normal nicotine cigarettes, although an inpatient study in which participants could only use VLNC cigarettes also demonstrated a reduction in smoke exposure 8.…”
Section: Common Questionsmentioning
confidence: 99%
“…Further, there was differential drop out for those with more severe nicotine dependence as evidenced by higher baseline Fagerström Test for Nicotine Dependence (FTND) scores. In more recent studies [10, 22], participants were excluded for having a serious medical or psychiatric disorder, other than depression.…”
Section: Introductionmentioning
confidence: 99%